Pengaruh Social Media Marketing, Brand Awareness, dan Persepsi Harga Terhadap Minat Beli - Fauziyyah, Anggia Nur; Mubarok, Dadan Abdul Aziz (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The increasingly competitive skincare industry need a companies for implement effective marketing way to enhance consumers’ purchase intention. The study needs to prove the impacts of Social Media Marketing, Brand Awareness, also Price Perception on Purchase Intention of Dermies by ERHA products in Bandung City. This research employed a quantitative approach and then survey methods, with primary data collected through questionnaire to 100 participants selected by purposive sampling. About this data analysis was conducted with multiples linear regression, supported by t-test also F-test to examine that hypotheses. The answer indicate, partially, Social Media Marketing give the positive then significant effects on Purchase Intention which is t-value of 5.569, Brand Awareness with a t-value of 5.378, and Price Perception with a t-value of 4.848, all showing significance values of 0.000 (<0.05). Simultaneously, Social Media Marketing, Brand Awareness, then Price Perception give a significant positive impact to Purchase Intention, as indicated from an F-value of 32.761 also a significance numbers of 0.000. The findings conclude that effective social media marketing ways, strong brand awareness, then favorable price perception play an crucial role to increasing consumers’ purchase intention toward Dermies by ERHA skincare products in Bandung City. Therefore, the results of this study are expected to provide practical implications for companies in designing integrated marketing strategies and serve as a reference for future research related to consumer purchase intention in the skincare industry.